2019
DOI: 10.21203/rs.2.13059/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Institutional Delivery Service Utilization And Associated Factors In Ethiopia: A Systematic Review And Meta Analysis

Abstract: Background: Different primary studies in Ethiopia showed the weight of institutional delivery service utilization and factors associated with it. However, variation among those studies was seen. This study was aimed to estimate the pooled national prevalence and associated factors of Institutional delivery service utilization in Ethiopia. Methods: PubMed, Cochrane library, Web of Science, and Google Scholar were searched. A funnel plot and Egger’s regression test were used to see publication bias. I-squared st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(69 reference statements)
3
2
0
Order By: Relevance
“…The odds of institutional delivery were higher among women whose age range from 15-19 years. This nding is in line to other reports from Ethiopia, Indonesia, Nepal, and ve other East African countries (12,15,20,23). For obvious reasons, young women are more educated and have a better knowledge on the direct and indirect causes of maternal mortality as well as the bene ts of institutional delivery.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The odds of institutional delivery were higher among women whose age range from 15-19 years. This nding is in line to other reports from Ethiopia, Indonesia, Nepal, and ve other East African countries (12,15,20,23). For obvious reasons, young women are more educated and have a better knowledge on the direct and indirect causes of maternal mortality as well as the bene ts of institutional delivery.…”
Section: Discussionsupporting
confidence: 89%
“…Long distances are usually having problems with waking distance, lack of transport, cost, and poor road infrastructure which might be making for rural women to decide on non-institutional delivery (2,3). Former studies from rural coastal Kenya and others reported that, distance to health facility was a fundamental barrier for institutional delivery and an independent factor for home delivery (3,12,14,15,22,23) which is in line to our study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, Somali, Afar, some parts of SNNP, Oromia, and Amhara also showed low institutional delivery. This finding is also consistent with a systematic review done in the country(9), EDHS 2016(5), spatial variation study in Northern Ethiopia, and EDHS 2005-2011 (41,42,43) Multilevel analysis of predictors: According to multilevel binary logistic regression analysis, women in the age group of 20-24, 25-29, and 30-34 years had higher odds of institutional delivery. Similar evidences were found in other studies in the country (45,40).…”
Section: Spatial Distributionssupporting
confidence: 88%